Human health risks assessment of toxic metals via water, food, and soil: A case study of Northern areas (Ghizer and Gilgit) of Pakistan - Nafeesa Khatoon; Sartaj Ali; Azhar Hussain; Jia Huang; Zengli Yu; Hongyan Liu (Results in Engineering)
Health concerns have arisen worldwide as a result of contaminated food and water. This study was aimed to determine the levels of selected heavy metals i.e. cadmium (Cd), chromium (Cr), copper (Cu) manganese (Mn), and nickel (Ni) in various sources such as drinking water, vegetables, and soil in districts Ghizer and Gilgit, Pakistan. Human health risks were assessed using deterministic indices, a probabilistic approach, and multivariate analysis. The determinations were carried out by spectrophotometrically (AAS-700, Perkin Elmer, USA) following the standard procedures for heavy metal levels. The mean concentration was recorded as Cd 0.036 mg/L, Cr 0.076 mg/L, and Ni 0.394 mg/L, respectively. It revealed an exceeded level for Cd (0.03 mg/L) and Cr (0.07 mg/L) against the safe limits in drinking water of Gilgit and Ghizer. The highest hazard quotient (HQ) was recorded as Cd 3000, Cr 3863.33, Cu 21.7, Mn 45.71, and Ni 22.35 for children regarding the consumption of vegetables from district Ghizer. Whereas higher HQ values were recorded for adults regarding consumption of vegetables from district Gilgit. A hazard index (HI) indicates significant non-carcinogenic health risks (HI > 1) in Ghizer and Gilgit drinking water and vegetables. Gilgit soil HI values exceeded more than one due to dermal contact, while HI > 1 due to oral and dermal exposure in Ghizer. Furthermore, drinking water samples and vegetables from both districts showed cancer risk (CR) > 1 × 10–4. The cumulative lifetime cancer risk (CR) was observed as 88.61 and 65.61 for adults whereas 2. 98 and 0.38 for children pertaining to vegetable consumption from Ghizer and Gilgit. It was found that the lifetime cancer risk (LCR) for Ghizer was higher than that for Gilgit, based on soil dermal and oral contact. Monte Carlo Simulation revealed adverse health risks in children as compared to adults. As a result of exposure to toxic metals, drinking water and vegetable consumption have higher cancer-causing risks. Therefore, we recommend that both districts implement strict monitoring regulations for drinking water and vegetables.